Extracellular vesicle surface engineering with integrins (ITGAL & ITGB2) to specifically target ICAM-1-expressing endothelial cells - Markus Bergqvist; Kyong-Su Park; Nasibeh Karimi; Lijuan Yu; Cecilia Lässer; Jan Lötvall (Journal of Nanobiotechnology)
Abstract Extracellular vesicles (EVs) are taken up by most cells, however specific or preferential cell targeting remains a hurdle. This study aims to develop an EV that targets cells involved in inflammation, specifically those expressing intercellular adhesion molecule-1 (ICAM-1). To target these cells, we overexpress the ICAM-1 binding receptor “lymphocyte function-associated antigen-1” (LFA-1) in HEK293F cells, by sequential transfection of plasmids of the two LFA-1 subunits, ITGAL and ITGB2 (CD11a and CD18). The LFA-1 receptor was strongly overexpressed on the EVs released by the transfected cells. We further loaded these EVs with a therapeutic peptide, targeting myeloid differentiation primary response 88 (Myd88; EVMyd88), through a developed EV open-and-close procedure. Myd88 is a downstream common intracellular messenger for most TLR-receptors. EV expression of LFA-1 increases EV binding to ICAM-1-expressing cells, an effect that was dose-dependently inhibited by a specific neutralizing ICAM-1 antibody. Further, activated human endothelial cells treated with LFA-1 EVMyd88 had increased uptake of these EVs, resulting in dose-dependent inhibition of induced release of IL-8, presumably by targeting Myd88. We conclude that LFA-1-expressing EVMyd88 may be a candidate suitable for delivering therapeutic peptides in inflammatory diseases associated with TLR-activation. Graphical Abstract